The Prospect of Stem Cells for HIV and Cancer Treatment: A Review - Khandaker Nujhat Tasnim; Sumiya Haque Adrita; Shahadat Hossain; Shahrukh Zaman Akash; Shazid Sharker (Mazandaran University of Medical Sciences, 2020)
Background: The news regarding the successful treatment of uncured diseases is extremely exciting. Recently, the study of stem cells has been widely considered. Objectives: The stem cells have the potential to be converted to all specialized functional cells. Methods: Advances in cell engineering and genetic reprogramming of the stem cells have contributed to novel approaches that may bring hope to HIV and cancer patients. Results: In this regard, HIV patients recently received a stem-cell transplant that replaced their white blood cells with HIV-resistant versions (obtained from stem cells). However, only a few clinically successful approaches are available on new stem cells. Conclusion: This review includes two parts; in the first section, the reader can obtain a basic idea about stem cells, whereas the second part emphasizes new opportunities and directions in translating stem cells basic research to the clinical applications.